Summary of recent economic developments in the middle east 1952-53 - United nations department of economic affairs (New York: United Nations Department of Economic Affairs, 1954)
The introduction to this summary endeavours to present an over-all view of main economic trends in the Middle East; as in previous years, this designation includes Afghanistan, Egypt, Iran, Israel, Jordan, Lebanon, Saudi Arabia, the Sudan, Syria, Turkey, Yemen; Aden Colony, Aden Protectorate, Behrein, Cyprus, Kuwait, Muscat and Oman, Qatar and Trucial Coast. Two chapters are devoted to major aspects of production and of petroleum. Three studies of individual countries- Egypt, Israel and Turkey- follow. Detailed and complete analysis of the various economic trends prevailing in the region and of the situation in each of the Middle East countries has not been attempted in this report. A more comprehensive study will be prepared in next years report, as was done in the review of economic conditions in the Middle East, 1951-52 and will include, inter alia, a survey of transport problems in the Middle East
Production and trade -- Petroleum -- Recent developments in Egypt -- Recent developments in Israel -- Recent developments in Turkey